Meracik Budaya-Menjaga Tradisi: Peran Perempuan Suku Dayak Siang dalam Produksi Popa - Rejeki, Delfiani Putri (Universitas Tanjungpura, 2025)
The production of popa among the Dayak Siang is an important space for women to preserve and transmit their culture through their knowledge of traditional alcohol production. Using a qualitative approach and anthropological perspective, this study aims to examine in depth the role of Dayak Siang women in the practice of popa production and their contribution to the preservation of local culture. The data in this study were obtained through participant observation and in-depth interviews, which were then analysed using Spradley's data analysis model. This study shows that Dayak Siang women not only play a role as domestic workers but also as innovators of tradition, preserving recipes passed down from generation to generation in the tradition of popa making. Through the kitchen as a multifunctional production space, women integrate household responsibilities, cultural values, and economic activities simultaneously. Knowledge about popa making is passed down across generations through two primary mechanisms: lineage-based transfer and learning-based transfer. This practice faces the challenges of modernity, which encourages a shift in production values from spiritual aspects to market orientation, potentially eroding the cultural values of popa. Nevertheless, Dayak Siang women demonstrate cultural resilience through the quality of popa, distribution restrictions, and spiritual ethics in the production of popa.